Mencari Definisi Hindu Nusantara - Kuckreja, Ravinjay; Yoga Segara, I Nyoman (Jayapangus Press, 2025)
Currently there is a dichotomy between Hindu India and Hindu Nusantara. This article seeks to find the meaning of Hindu Nusantara, a term used by Indonesian Hindus, including in government policy-making, in the absence of a clear definition. The research employed a qualitative approach, utilizing theoretical analysis and document research to explore the historical evolution and contemporary expression of Hinduism in Indonesia. Agama Hindu Indonesia rejects international Hindu missionary movements, although it is also a national missionary movement. This missionary activity results in the first definition of Hindu Nusantara; a local ancestral religion that becomes a sect or part of Agama Hindu Indonesia. However, since indigenous religions can be recognized as belief systems (aliran kepercayaan), Hindu Nusantara turned into a counter-movement to Hindu missionaries from India. Similar to Islam Nusantara, it became a form of Hinduism that resonates with Indonesian customs and culture. This research also discusses the possible impacts of Hindu Nusantara; (1) the return of Hindu Nusantara sects to ancestral religion, (2) increased intolerance towards Indians and their form of Hinduism, and (3) Balinese preferring to opt out of Hinduism altogether to assert their own religious identity. The phenomenon of Hindu Nusantara suggests that movements within Indonesian Hinduism are often reactive, lacking thoughtful insight, in-depth study, and careful discernment.